Junk Food Consumtion : A Key Driver of The Obesity Epidemic - adyani, asta (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: . Obesity in adolescents is still an epidemic problem for the next 10 years. The Key lifestyle components such as physical activity, dietary habits, sleep patterns, and screen time that contribute to the rising prevalence of obesity. The Purpose of the study was to investigate corelation between behaviour Lyfestyle and Level of Obesity. Methods: We conducted a cross sectional study involving 185 adolescents male and female (13-19 years) who Particpated the validates self reported about Health behaviour. The Questionare allows the Malaysian Adolescents Health Survey. The inclusion Criteria is adolescents in range of age 13-19 years old there were Leave in Indonesia. Bivariate Analysis used Person Corelation was conducted. Analysis used SPSS 25 aplication. Results: We identified 185 adolescents. the mean Age are 12.27 years (SD 3.756). Majority respondents are female 122 (65.9%), Overweight and obesity are significant issues: 10.8% (20 adolescents) are overweight (BMI > 25–27). 18.9% (34 adolescents) are classified as obese (BMI > 27). Together, 53.5% of the adolescents (99 individuals) have a BMI above the normal range. There is a strong positive correlation between junk food consumption and BMI, as indicated by the Pearson correlation coefficient of 0.877. This value suggests that higher junk food consumption is strongly associated with higher BMI. The p-value (Sig. 2-tailed) is 0.000, which is highly statistically significant (p < 0.01). The findings highlight a significant positive correlation between junk food consumption and obesity among adolescents, supported by a strong Pearson correlation coefficient of 0.877. This relationship underscores the critical role of dietary behaviors in adolescent obesity, a growing public health issue worldwide Conclusion: The findings emphasize the need for public health interventions, such as education on healthy eating, regulating junk food advertising targeted at youth, and promoting healthier food environments at schools.